2010
DOI: 10.1103/physrevd.81.074019
|View full text |Cite
|
Sign up to set email alerts
|

Quantum interactions between nonperturbative vacuum fields

Abstract: We develop an approach to investigate the nonperturbative dynamics of quantum field theories, in which specific vacuum field fluctuations are treated as the low-energy dynamical degrees of freedom, while all other vacuum field configurations are explicitly integrated out from the path integral. We show how to compute the effective interaction between the vacuum field degrees of freedom both perturbatively (using stochastic perturbation theory) and fully nonperturbatively (using lattice field theory simulations… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2010
2010
2011
2011

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Ref. [5,10] ) one arrives to an expression in the form of Eq. ( 3), where the effective Hamiltonian H(γ 1 , .…”
Section: The Vacuum Manifold Projection Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Ref. [5,10] ) one arrives to an expression in the form of Eq. ( 3), where the effective Hamiltonian H(γ 1 , .…”
Section: The Vacuum Manifold Projection Methodsmentioning
confidence: 99%
“…Indeed, in Ref. [10] it was shown that once the system of Eq.s (11) is satisfied in one gauge, it holds also in any other gauge.…”
Section: The Vacuum Manifold Projection Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…ones based on different types of vacuum field configurations. The details of the method briefly illustrated here will be presented in a forthcoming paper [4].The extension of the present formalism to QCD is presently in progress.…”
Section: Discussionmentioning
confidence: 99%